Using QGIS for organising, visualising and publishing in situ observations, drone mosaics and satellite imagery of Arctic sea ice ... - Olaussen, Tor I.; Hamre, Torill; Monsen Frode (Zenodo, 2022)
This report documents how QGIS was installed and used at NERSC in the Digital Arctic Shipping project to organise, visualise and publish sea ice data from several sources. QGIS is an open-source Geographic Information System (GIS) that is available on all major computer platforms, and maintained by a large community world-wide contributing to the Open Source Geospatial Foundation (OSGeo). We have used QGIS Desktop, a GIS running on a local computer, to organise sea ice data in different formats, spatial resolutions, and map projections into a coherent structure. This structure is called a QGIS project, which in addition to listing the individual data layers defines how data can be published through a standard interface in a given map projection and format. By organising related sea ice data in a QGIS project, we can publish them using the QGIS Server application. This allows users to visualise and access the data through their web browser without having to install any local software or plugins. Together, ... : NERSC Technical Report no 419. This work has been financed by the Research Council of Norway through the Digital Arctic Shipping project (Project No. 309708). ...